Predictors of re-employment and quality of life in NHS staff one year after early retirement because of ill health; a national prospective study. Issue 7 (18th June 2004) - Pattani, S; Constantinovici, N; Williams, S
Abstract : Aims: To measure changes in health related quality of life and employment status of NHS staff one year after early retirement because of ill health, and to identify predictors of re-employment. Methods: A national cohort of 1317 NHS staff taking early retirement because of ill health in 1998 was recruited. Postal questionnaires were used to assess their quality of life (SF-36) and employment status 12 months after retirement. Results: A total of 1143 (87%) ill health retirees responded; 152 (13%) retirees were working at one year, mostly part-time, and 22% of them were re-employed by the NHS. Independent predictors of re-employment were: living in England rather than Wales and occupation of doctor. There was an increased likelihood of re-employment with reducing age and increasing quality of life at baseline. Retirees' quality of life improved from baseline to one year after ill health retirement, but at one year still remained lower than the general population. Improvements in physical and mental component scores were greater in those working at one year compared with those not working. Conclusion: Reducing ill health retirement is likely to be of benefit to the individual, the NHS, and the economy. Results suggest that such a reduction may be possible and the identified predictors of re-employment may help in this process.